2016
DOI: 10.2989/10220119.2016.1170727
|View full text |Cite
|
Sign up to set email alerts
|

The potential of replacing conventional dairy supplements with forage legume-based diets in Zimbabwe’s smallholder dairy sector

Abstract: The effect of replacing commercial supplements with isoenergetic and isonitrogenous velvet bean-, cowpeaand lablab-based supplements on milk yield, milk quality and economic returns in smallholder crossbred dairy cows was investigated in the 2013 and 2014 dry seasons. Using 3 × 3 Latin square designs, nine multiparous Red Dane, Guernsey and Holstein-Friesian crosses in mid-lactation (130 ± 19 d) were offered forage legume-based supplements for 63 d at 0.5 kg per litre of milk produced. Milk quantity and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Studies in Malawi and Zambia have shown a high yield advantage of over 1 tonne per hectare [20,34]. Livestock productivity has been enhanced through supplementary feeding with forage legumes, such as the velvet bean (Mucuna pruriens), cowpea (Vigna unguiculata (L.), lablab (lablab purpureus), and browse legumes, such as the acacia (Senegalia and Vachellia), and the Calliandra and Leucaena trees [26,35], which are promoted by the International Livestock Research Institute (ILRI) and World Agroforestry Centre (ICRAF), in collaboration with Nongovernmental Organisations (NGOs) and government departments. Researchers have reported increased benefit cost ratios of 1.12-3.03 in Zimbabwe [36].…”
Section: Significance Of Csa In Crop-livestock Smallholder Farming Symentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Malawi and Zambia have shown a high yield advantage of over 1 tonne per hectare [20,34]. Livestock productivity has been enhanced through supplementary feeding with forage legumes, such as the velvet bean (Mucuna pruriens), cowpea (Vigna unguiculata (L.), lablab (lablab purpureus), and browse legumes, such as the acacia (Senegalia and Vachellia), and the Calliandra and Leucaena trees [26,35], which are promoted by the International Livestock Research Institute (ILRI) and World Agroforestry Centre (ICRAF), in collaboration with Nongovernmental Organisations (NGOs) and government departments. Researchers have reported increased benefit cost ratios of 1.12-3.03 in Zimbabwe [36].…”
Section: Significance Of Csa In Crop-livestock Smallholder Farming Symentioning
confidence: 99%
“…Some CSA technologies are labour-saving and, as such, they help to avail labour for other off-farm activities that can generate an income for the household. (35). In this case, the food consumed in the previous 7 days was considered.…”
Section: Specification Of the Empirical Modelmentioning
confidence: 99%
“…Mucuna is mainly used as a green manure (Mhlanga et al, 2015) and for cattle feed (Jiri, 2003) to increase milk production and body score (Murungweni et al, 2004). Due to its high forage production rate, mucuna is increasingly becoming a viable option to supply supplementary feed for the smallholder farmers' livestock (Gwiriri et al, 2016). Feeding livestock with forage legumes reduces the cost of producing milk and increases income by 50 % compared to where commercial feeds are used (Murungweni et al, 2004;Chakoma et al, 2016;Gwiriri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…During such periods, cattle graze on crop residues left in the fields after harvesting and most of the manure that accumulates in the kraals is applied to the vegetable plots (Nzuma, 2013). The bulk of the feed resource for smallholder cattle during the dry season is communal rangelands, which are poor in feed quality and quantity, thus negatively affecting productivity (Gwiriri et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Research on crop livestock integration in West Africa has led to an increase in the amount of crop residues fed to livestock (Sempore et al ., 2016). Studies of crop–livestock integration in smallholder dairy farming and beef systems have indicated positive results, with the assertion that marketing is important for the uptake and enhanced impact of integrated crop–livestock integration strategies in smallholder systems (Gwiriri et al ., 2016). Despite these studies, adoption of crop–livestock integration strategies is still low, which has been attributed to lack of clear demonstration of the benefits of appropriate crop–livestock integration.…”
Section: Introductionmentioning
confidence: 99%